Sperm Viability and Acrosome Integrity by Conventional and Fluorescent Staining Techniques Recovered in Three Different Buffers from Sheep Epididymal Tail- A Preliminary Study - Rasool Bhat, Ghulam; Ahmad Lone, Farooz; Preet Singh, Pawan; Rana, Sanchi (The Indian Journal of Animal Reproduction, 2025)
The study was carried out to evaluate the accuracy of conventional and fluorescence based staining techniques for via bility and acrosome integrity of cauda epididymal spermatozoa in sheep. Spermatozoa were recovered from fresh epi didymis of testicles collected from local slaughter houses. Spermatozoa were recovered in seminal plasma (SP), Tyrode’s  Albumin Lactate Pyruvate (TALP) and Tris Methyl Aminomethane (TRIS) buffer. The recovered spermatozoa were eval uated immediately and stored at 4 °C for subsequent evaluation up to 72 hours. Sperm viability and acrosome integrity  were assessed at 0, 24, 48 and 72 hours of recovery, using Eosin-Nigrosin and Carboxyfluorescein Diacetate (CFDA) plus  Propidium Iodate (PI) for viability while Giemsa and Fluorescein Isothiocyanate-Peanut Agglutinin (FITC-PNA) plus  PI for acrosome integrity. Upon general linear model statistics, the interactions viz; time x technique and buffer x time  x technique were significant when TALP recovered spermatozoa were evaluated for viability and acrosome integrity, and  when TRIS recovered spermatozoa were evaluated for acrosome integrity. By comparing the results at different periods,  it was observed that the percentage values of both viability and acrosome integrity in SP recovered spermatozoa were  significantly higher (p
Keywords: Acrosome integrity; conventional; fluorescent probes; recovery buffer; sperm